009 Asymmetric peri-optic cerebrospinal fluid space distension in cluster headache. Issue 9 (12th August 2022) - Farag, Mena; Yeung, Joshua Au; Heller, Simon; Virgo, Jonathan; Childs, Lucy; Oliver, Rupert
Abstract : Distension of the optic nerve sheath is a typical neuroimaging finding seen associated with elevated intracranial pressure and a hallmark MRI feature of papilloedema. Cases of asymmetric and unilateral papilloedema have been reported though the pathophysiological mechanism remains unclear and may be multifactorial. We present a patient in her mid-thirties with episodic cluster headaches with left peri-optic nerve cerebro- spinal fluid (CSF) sheath distension identified on MRI head and orbits. No obstructive lesion was identified at the orbital apex. Optical coherence tomography revealed bilateral mild symmetrical subclinical optic nerve thinning. Optic nerve function, assessed with acuity, Ishihara colour vision and Goldman perimetry, was normal bilaterally. CSF opening pressure measured 23.5 cm H2O and constituents were bland. To our knowledge, this is the first description of asymmetric peri-optic CSF space distension in cluster headache with ipsilateral clinical and radiological phenomena. The findings raised the possibility of an asymmetric presentation of elevated intracranial pressure. Our patient, however, had no clinical or other radiological features suggestive of this. The radiological findings ipsilateral to our patient's cluster headaches raises the difficult question about a causal relationship or simply a mere coincidence between the clinical and radiological picture.